Perbandingan Karakteristik Marshall Aspal Karet (Natural Rubber Modified Asphalt) Dan Aspal Penetrasi 60/70 Pada Campuran Asphalt Concrete - Wearing Course (AC-WC) Menggunakan Aggregat Lokal Madura - Taurina Jemmy Irwanto; Nurul Lia Suryani; Sendika Renaldi (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2023)
Road damage in Indonesia is generally caused by excessive loading. One type of hot asphalt that receives the load directly from the vehicle is AC-WC (Asphalt Concrete - Wearing Course), ACWC. to hot mix asphalt and to reduce production costs and asphalt layer strength. natural rubber asphalt mixture for road asphalt can increase asphalt pavement in terms of service life and resistance to grooves, asphalt has a better pavement level, is not easy to leave wheel tracks when asphalt is wet, and has higher durability than ordinary asphalt. This will determine the longevity of the pavement. Based on this explanation, the use of local materials is expected to reduce production costs and reduce the traffic load of the road network that has been passed to transport materials from outside the island of Madura. In this further research, we will study the comparison of the use of Natural Rubber Modified Asphalt and 60/70 penetration asphalt using Madura local aggregates against the AC-WC hot asphalt mixture, which is expected to produce hot asphalt mixtures made from local and natural materials so that they have strength. the good one. From the test results on all types of mixtures, the optimal mixture was obtained at 4.9% asphalt content with the highest stability value of 1040 kg with a VIM value of 4.43%, VMA 15.91%, VFB 72.12%, MQ 300Kg/mm, and the density value is 2.252 gr/cc.